2010
DOI: 10.1089/thy.2009.0128
|View full text |Cite
|
Sign up to set email alerts
|

Visual Abilities at 6 Months in Preterm Infants: Impact of Thyroid Hormone Deficiency and Neonatal Medical Morbidity

Abstract: Our findings signify that some of the weak visual abilities in preterm infants can be accounted for, in part, by their reduced TH levels in the early postnatal period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0
16

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 36 publications
3
15
0
16
Order By: Relevance
“…On the other hand, in a study on preterm infants, Simic et al [20] reported slow blue-yellow and red-green color vision enhancement. Also, albeit rare, male patients are color blind in TH resistance syndrome, which represents a model for fetal hypothyroidism.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, in a study on preterm infants, Simic et al [20] reported slow blue-yellow and red-green color vision enhancement. Also, albeit rare, male patients are color blind in TH resistance syndrome, which represents a model for fetal hypothyroidism.…”
Section: Discussionmentioning
confidence: 94%
“…The reason is TH effects on the developing fetus change depending on the time frame of TH deficiency. In this regard, transient hypothyroxinemia of prematurity has been linked to suboptimal neurodevelopment [20] . Similarly, cone differentiation and opsin expression are already effected in the fetal period in TH resistance syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…cerebral palsy [13,[37][38][39][40][41]. In the study groups with a positive effect of L-thyroxine on the development of preterm babies, a dose of 6-8 μg/kg body weight was used, slightly improving mental development after 5-10 years.…”
Section: Szkolenie Podyplomowementioning
confidence: 99%
“…Niemniej liczne kohortowe badania retrospektywne dokumentują związek między hipotyroksynemią i opóźnieniem rozwoju psychoruchowego wcześniaków oraz występowaniem w tej grupie mózgowego porażenia dziecięcego [13,[37][38][39][40][41]. W dotychczas obserwowanych grupach, w których stwierdzono pozytywny wpływ leczenia L-tyroksyną na rozwój wcześniaków, stosowano dawkę 6-8 μg/kg masy ciała, co powodowało nieco lepszy rozwój umysłowy widoczny po 5-10 latach.…”
unclassified
“…While clinically apparent visual dysfunction is not a classic feature of congenital primary hypothyroidism, transiently low TH levels in preterm infants have been associated with visual deficits at 6 months of (corrected) age. 19 Furthermore, hypothyroidism may affect vision more in the setting of coexisting optic nerve disease than it does in isolation. For example, our clinical registry study of subjects with ONH demonstrates that most children with ONH experience some degree of spontaneous improvement in vision during the first few years of life 4,20 ; we hypothesize that low circulating TH levels may preclude vision improvement in previously compromised optic nerves that are already at risk for reduced vision.…”
mentioning
confidence: 99%